1975
DOI: 10.1099/00221287-90-2-191
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Formation and Stability of D-Glucoside 3-Dehydrogenase Activity in Cultures of Agrobacterium tumefaciens

Abstract: SUMMARY D-Glucoside 3-dehydrogenase specific acivity in Agrobacterium tumefaciens was maximal towards the end of the exponential growth phase of batch cultures; over go % of the activity disappeared within the next 15 h. Manganese ions, although essential for growth of the organism, strongly repressed D-glucoside 3-dehydrogenase synthesis in sucrose medium but had little effect when the carbon source was methyl a-D-glucoside. D-Glucoside pdehydrogenase activity increased linearly with increasing specific growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…These authors that Mn2+ raised the efficiency of ATP utilization for growth. On the contrary, Kurowski et al (1975) demonstrated that D-aldohexoside:cytochrome c oxidoreductase activity was affected by the amount of Mn2+ in the medium depending upon the carbon source. Mn2+ (lo4 M and more) strongly decreased the synthesis of D-a1dohexoside:cytochrome c oxidoreductase in sucrose medium but had little effect when the carbon source was methyl a-D-glucoside.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These authors that Mn2+ raised the efficiency of ATP utilization for growth. On the contrary, Kurowski et al (1975) demonstrated that D-aldohexoside:cytochrome c oxidoreductase activity was affected by the amount of Mn2+ in the medium depending upon the carbon source. Mn2+ (lo4 M and more) strongly decreased the synthesis of D-a1dohexoside:cytochrome c oxidoreductase in sucrose medium but had little effect when the carbon source was methyl a-D-glucoside.…”
Section: Discussionmentioning
confidence: 91%
“…Although several physiological functions have been attributed to 'Author to whom all correspondence should be addressed the 3-ketoglucoside metabolism (Miyairi and Fukui 1973;Chern et al 1976aChern et al , 1976b, the essential role of this pathway has occasionally been questioned (Kurowski and Pirt 1971;Kurowski et al 1975).…”
Section: Introductionmentioning
confidence: 98%
“…duced cells. Sym-Contrasting effects of a-methylglucoside and ith succinate; (0) sucrose on ACO development in A. tumefaciens treatment; (x) c-cells have also been reported by Kurowski et al ,eated; and (A) a-(15). They noted that cells grown in a chemolls.…”
mentioning
confidence: 60%
“…iuired to initiate Succinate inhibition of ACO synthesis has also enzyme activity been observed by Kurowski et al (15). The of cells to appro-inhibition appears to be specifically directed to ition of protein ACO induction since glucosidase synthesis is blocks enzyme unaffected.…”
Section: _x Xmentioning
confidence: 86%